1991
DOI: 10.1021/bi00227a025
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of a minimal potassium channel expressed from a synthetic gene

Abstract: A gene for a slowly activating, voltage-dependent K(+) -selective channel was designed and synthesized on the basis of its known amino acid sequence. The synthetic gene was cloned into a transcription vector, and in vitro transcribed mRNA was injected into Xenopus oocytes for electrophysiological assay of the resulting ionic currents. The currents are voltage-dependent and highly selective for K+ over Na+. The selectivity among monovalent cations follows a familiar K(+)- channel sequence: K+ greater than Rb+ g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0
1

Year Published

1993
1993
2001
2001

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 39 publications
(56 reference statements)
3
24
0
1
Order By: Relevance
“…The lack of an apparent voltage sensor and the small size of IsK with a single membrane spanning domain created skepticism of its potassium channel function when its clone first appeared (Hausdorff, Goldstein, Rushin, and Miller, 1991;Goldstein and Miller, 1991). The study of mutations of this channel even revealed that only part of this protein was sufficient to generate its potassium channel activity (Takumi, Moriyoshi, Aramori, Ishii, Oiki, Okada, Ohkubo, and Nakanishi, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of an apparent voltage sensor and the small size of IsK with a single membrane spanning domain created skepticism of its potassium channel function when its clone first appeared (Hausdorff, Goldstein, Rushin, and Miller, 1991;Goldstein and Miller, 1991). The study of mutations of this channel even revealed that only part of this protein was sufficient to generate its potassium channel activity (Takumi, Moriyoshi, Aramori, Ishii, Oiki, Okada, Ohkubo, and Nakanishi, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that despite the remarkably diverse array of membranes ( e g from bacteria, plants, and animals) that have retained this channel pore sequence in K+ channels, there is a nove1 exception to this molecular basis for selective K+ conductance. A small (130 amino acids, approximately 15 kD) protein (the "mink" or minimal K+ channel) has recently been identified in mammalian kidney, uterus, and heart that is structurally unrelated to the ubiquitous, large family of 70-kD K+ channels that share the conserved selectivity filter (Hausdorff et al, 1991).…”
Section: Lmmunodetection Of K+ Channel Proteins In the Lnner Envelopementioning
confidence: 99%
“…Members of the second K ÷ channel type have been termed minK channels [2]. This type of channel has been originally cloned from rat kidney and was subsequently found in heart and uterus tissue of different species [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%